2019
DOI: 10.1186/s12889-019-6907-x
|View full text |Cite|
|
Sign up to set email alerts
|

Economic burden of multiple sclerosis in a population with low physical disability

Abstract: Background In multiple sclerosis (MS), half of affected people are unemployed within 10 years of diagnosis. The aim of this study was to assess the economic impact of MS in adult subjects with relapsing-remitting MS (RRMS) and primary progressive MS (PPMS). Methods A multicenter, non-interventional, cross-sectional study was conducted. The Expanded Disability Status Scale (EDSS) and the 23-item Multiple Sclerosis Work Difficulties Questionnaire (MSWDQ-23) were used to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 27 publications
1
28
0
1
Order By: Relevance
“…One systematic review reported that annual indirect costs of MS per patient can range from US$2000 (when including sick leave, disability and workers’ compensation) to US$20,000 (when including costs of work time missed, underemployment and episodes of unemployment due to disability) [ 15 ]. Even individuals who experience only mild physical disability from MS have substantial costs associated with sick leave, work absenteeism and premature retirement [ 16 ]. Individuals with MS experience financial strain from reduced income due to missed work or early retirement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One systematic review reported that annual indirect costs of MS per patient can range from US$2000 (when including sick leave, disability and workers’ compensation) to US$20,000 (when including costs of work time missed, underemployment and episodes of unemployment due to disability) [ 15 ]. Even individuals who experience only mild physical disability from MS have substantial costs associated with sick leave, work absenteeism and premature retirement [ 16 ]. Individuals with MS experience financial strain from reduced income due to missed work or early retirement.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with MS experience financial strain from reduced income due to missed work or early retirement. Employers are burdened by reduced productivity and workers’ compensation payments, while the economy suffers from labor force reductions and bears the costs of paying out disability benefits [ 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sclerosis (MS) is a chronic inflammatory demyelinating disease of the central nervous system associated with disability progression and a high impact on patients' daily activities and quality of life (HRQoL) [1,2]. The cause of MS is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Its prevalence has substantially increased in the last three decades and it affects ~2.3 million people worldwide ( 1 , 2 ). The disease is associated with a high economic burden for society, and Spain is the European country with the highest total annual cost per patient ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%